2005
DOI: 10.1016/j.contraception.2004.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of five nonoxynol-9 spermicides

Abstract: Objective-To examine the acceptability of five nonoxynol-9 (N-9) spermicides.Methods-We analyzed data from a randomized trial of five products, including three gels containing different amounts of N-9 per dose, a film and a suppository. In the trial, 1536 participants were asked to use the assigned spermicide for 7 months and to complete questionnaires 4 weeks after admission and at discontinuation.Results-Overall, 43% of participants liked their spermicide "very much." This proportion was higher in the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…We report that 89% of African women who used the placebo vaginal film liked using it, and 87% said they would definitely use a vaginal film for protection against HIV infection. This is similar to the percentage of American women (81% of 273), 5 South African women (75% of 20), 6 and Cameroonian women ( > 80% of 520) 7 who liked using the N-9 spermicidal film. In our study, 72% of African women found the placebo film easy to insert, 28% found it difficult to insert because it stuck to the fingers, and some women thought an applicator would be beneficial.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We report that 89% of African women who used the placebo vaginal film liked using it, and 87% said they would definitely use a vaginal film for protection against HIV infection. This is similar to the percentage of American women (81% of 273), 5 South African women (75% of 20), 6 and Cameroonian women ( > 80% of 520) 7 who liked using the N-9 spermicidal film. In our study, 72% of African women found the placebo film easy to insert, 28% found it difficult to insert because it stuck to the fingers, and some women thought an applicator would be beneficial.…”
Section: Discussionsupporting
confidence: 82%
“…Leakage was reported by 55% of placebo film users in our study compared with 23% of American N-9 film users who reported leakage or messiness. 5 Almost all (97%) users of the placebo film thought that the product increased or had no effect on their own sexual pleasure compared with 86% of American N-9 film users. 5 Seven percent of women surveyed said their male sex partners disliked them using the placebo film compared with 20% of American women who reported partner dissatisfaction with the N-9 film.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although some studies have investigated acceptability in terms of product-related factors, such as color and consistency; delivery method; product form; application process; messiness; lubrication; potential for adverse reactions; and effects on sexual pleasure (Hammett et al, 2000;Hardy, Jimenez, de Padua, & Zaneveld, 1998;Hira et al, 1995;Mason et al, 2003;Raymond et al, 2005), little is known about inter-and intra-personal psychological aspects that affect acceptability and use (Severy, Tolley, Woodsong, & Guest, 2005;Ramjee et al, 2006). Very few studies have assessed male partner acceptance of a vaginal microbicide used during sex or investigated the link between male partner acceptance and female acceptance (Bentley et al, 2004;CarbelloDieguez et al, 2007;Mantell et al, 2005;Low-Beer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%